Influences on HPV vaccination across levels of the social ecological model: perspectives from state level stakeholders. Issue 4 (3rd April 2021) - Ryan, Grace; Avdic, Lejla; Daly, Eliza; Askelson, Natoshia; Farris, Paige E.; Shannon, Jackilen; McRee, Annie-Laurie; Hanson, Jessica; Kenyon, DenYelle Baete; Seegmiller, Laura
ABSTRACT: Nationally, human papillomavirus (HPV) vaccination rates fall short of the Healthy People 2020 goal of 80% completion. Although strategies to increase these rates exist, low rates persist. We used concept mapping with state-level stakeholders to better understand barriers and facilitators to HPV vaccination. Concept mapping is a participatory research process in which respondents brainstorm ideas to a prompt and then sort ideas into piles. We present results of the brainstorming phase. We recruited participants identified by researchers' professional connections (n = 134) via e-mail invitations from five states (Iowa, South Dakota, Minnesota, Oregon, and Washington) working in adolescent health, sexual health, cancer prevention and control, or immunization. Using Concept Systems' online software we solicited participants' beliefs about what factors have the greatest influence on HPV vaccination rates in their states. From the original sample 58.2% (n = 78) of participants completed the brainstorming activity and generated 372 statements, our team removed duplicates and edited statements for clarity, which resulted in 172 statements. We coded statements using the Social Ecological Model (SEM) to understand at what level factors affecting HPV vaccination are occurring. There were 53 statements at the individual level, 22 at the interpersonal level, 21 in community, 51 in organizational, and 25 in policy. Our results suggest that a tiered approach, utilizing multi-level interventions instead of focusing on only one level may have the most benefit. Moreover, the policy-level influences identified by participants may be difficult to modify, thus efforts should focus on implementing evidence-based interventions to have the most meaningful impact.